(untitled) - Packer, James Innell; (1926-2020) (U.S.A., 1961)
If God is in control of everything, can Christians sit back and not bother to evangelize? Or does active evangelism imply that God is not really sovereign at all? J.I. Packer shows in this classic study how both of these attitudes are false. In a careful review of the biblical evidence, he shows how a right understanding of God's sovereignty is not so much a barrier to evangelism as an incentive and powerful support for it.
Keywords: Providence and government of God